Penina, infamous man: History and subjectivity in El fusilamiento de Penina, by Aldo Oliva (El Taco en la Brea, 2023)
This article intends to study El fusilamiento de Penina, the only book by the Argentinian poet Aldo Oliva (1927‒2000) not composed of poems; instead, it is about a research on the illegal shooting of the anarchist worker Joaquín Penina, in 1930, by Uriburu’s dictatorship. Finished in 1975, the book was confiscated and burnt by the dictatorship of 1976, and remained lost until 2004. After a reconstruction of Penina’s story and of Oliva’s book, the text analysis is focused on an evidence: in the investigation the traces of Penina’s subjectivity, and those of Oliva himself, are deliberately erased, leaving their place to the study of «objective conditions» and to the «objectivity» of de researcher. This fact sharply contrasts with the subjectivist vision of history that one can find among Oliva’s poems, and also differs from others examples of the genre, that elaborate in other ways the marks of subjectivity and the entanglement between testimony and fiction. To exemplify this contrast, the article finishes with a coda that analyses a poem by Oliva about a figure that could be thought of as the reverse or the negative of Penina: Severino Di Giovanni, the expropriator anarchist.
Keywords: Aldo Oliva; Joaquín Penina; Argentinian History; Anarchism; Infamous Decade